Alleviation of apoptosis of bone marrow-derived mesenchymal stem cells in the acute injured kidney by heme oxygenase-1 gene modification. (December 2015) - Liu, Nanmei; Wang, Huiling; Han, Guofeng; Tian, Jun; Hu, Weifeng; Zhang, Jinyuan
Highlights: AKI microenvironment is adverse for survival of BMSCs. HO-1 overexpression alleviates apoptosis of BMSCs. Anti-oxidant via the inactivations of p53 and p38MAPK and the anti-inflammation joins in the HO-1 overexpression effect. Improved HO-1-BMSCs survival results in the improvement of the renal function of AKI rats. Abstract: Bone marrow-derived mesenchymal stem cells (BMSCs) transplantation is beneficial for the treatment of acute kidney injury (AKI), but the poor survival of BMSCs limits the repair effect. The oxidative stress in the AKI microenvironment is regarded as the main reason. Considering the potent anti-oxidant ability of heme oxygenase-1 (HO-1), HO-1 overexpression in BMSCs can be expected to improve the survival of BMSCs and correspondingly enhance the AKI repair effect. Here, BMSCs are transfected with pLV-HO-1/eGFP and pLV–eGFP by the lentivirus vector to get HO-1-BMSCs and eGFP-BMSCs, respectively. Ischemia/reperfusion-AKI kidney homogenate supernatant (KHS) is prepared for treating BMSCs, eGFP-BMSCs and HO-1-BMSCs. AKI-KHS results in a high inhibitory rate of BMSCs growth and a high proportion of TUNEL positive BMSCs, while HO-1 overexpression inverses this phenomenon and re-establishes the antioxidant and oxidant balance in HO-1-BMSCs. Phosphorylations of p53 and p38 mitogen-activated protein kinases (p38 MAPK) in HO-1-BMSCs decrease. Lower levels of monocyte chemotactic protein 1, tumor necrosis factor-α and interleukin 1β are also observed in supernatant of HO-1-BMSCs. The in vivo study shows that HO-1 overexpression sharply decreases the apoptosis of BMSCs in the injured kidney, and correspondingly the renal function of the AKI rats improves significantly. In conclusion, BMSCs with HO-1 overexpression suggests a better survival in the I/R-AKI microenvironment and a better kidney repair effect. The anti-oxidant effect via the inactivations of the downstream p53 and p38MAPK in BMSCs and the anti-inflammation could be the mechanisms. It provides a novel approach for the cell-based AKI-therapy.